Diffuse large B-cell lymphoma-germinal center B cell subtype presenting as cutaneous nodules - Manickam, Navakumar; Reddy, Mayani Lakshmi Priya; Vellaisamy, Seethalakshmi Ganga; Gopalan, Kannan (Journal of Pakistan Association of Dermatologists, 2024)
Diffuse large B cell lymphoma (DLBCL) is the most common type of non-Hodgkin lymphoma worldwide, representing approximately 30-40% of all cases in different geographic regions. We report a case that highlights the atypical presentation of DLBCL-germinal centre B cell subtype as a cutaneous disease. This unique presentation emphasizes the importance of considering DLBCL in the differential diagnosis of patients presenting with infiltrated skin lesions in the absence of classic lymphadenopathy.